Comparative Study of Primary Productivity Based on Oxygen Method in The Tanjung Kudu Lake and Parit Lake Kampar Regency, Riau Province - Clara Novicasari Br Surbakti; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTPrimary productivity is the conversion of solar energy and nutrients to living biomass through photosynthesis. A research aimed to understand the comparisons of community activities to primary productivity in Tanjung Kudu Lake and Parit Lake. This research was conducted in December 2020.There were three sampling stations namely inlet area, in the middle of the lake and in the end of the lake.In each stations, there were 2 sampling point, in the surface and 2 Secchi depth. Sampling was done three times, once per week.Primary productivity based on oxygen method in the Tanjung Kudu Lake was 344,44-509,72 gC/m3/day and in the Parit Lake was 366,66-539,58 gC/m3/day. Water quality parameter such as transparency46-67cm, temperature 29-30oC, pH 5-6, dissolved oxygen 2,9-5,3 mg/L, CO27,99-15,99mg/L, nitrate 0,0133-0,064mg/L and phosphate 0,0130-0,064mg/L while in Lake Parit the transparency was 47,5-67,5 cm, temperature 29-30oC, pH 5-6, dissolved oxygen 3,3-5,2 mg/L, CO27,99-15,99 mg/L, nitrate 0,022-0,054 mg/L and phosphate 0,024-0,050 mg/L.Based on two way anova statistical test of primary productivity was not significantly different between stations and over time. Based on the abundance of primary productivity, Tanjung KuduLake and ParitLake can be categorized as mesotrophic. Keywords:Primary productivity, Water Quality, Tanjung Kudu Lakes, Danau Parit Lakes,Mesotrophic